FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN UTANG PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Christine Dwi Karya Susilawati; Lidya Agustina; Se Tin (University of Merdeka Malang, 2012)
In the last several years, there had been an increase on the research emphasized on the agent-principal conceptat financial corporation. The objective of this research was to test empirically the agency concept and theirrelation toward the debt policy of corporations. This research analyzed the factors influencing debt policy atmanufacturing firms in Indonesia. Analyzing instruments in this research was multiple regression analysis.The result of this research showed that firm size, profitability and free cash flow had significant influence todebt policy while managerial ownership, institutional ownership, dividend policy and structure asset did nothave significant influence to debt policy. However, simultaneously the seven variables had significant influenceto debt policy.